Alternative splicing and the inhibition of splicing kinases in Alzheimer’s Disease - Alalwany, Roaa (2021)
Alzheimer’s disease (AD) is the most common cause of dementia, the chronic and progressive deterioration of memory and cognitive abilities. AD can be pathologically characterised by neuritic plaques and neurofibrillary tangles, formed by the aberrant aggregation of β-amyloid and tau proteins, respectively. As the global population living with dementia is projected to reach 132 million by the year 2050, treatment of AD has become a top public health priority. Unfortunately, there are currently no disease-modifying drugs available for AD patients, so it is critical to develop novel therapeutic strategies for better disease management.